An Appraisal of Reflective Teaching Practice among Secondary School Islamic Studies Teachers in Ilorin, Kwara State - Asmau Imam Abdulkabir (Presscience, 2023)
The main purpose of this study is to investigate the level of Islamic studies teachers’ reflection on the Qur’an and Prophetic Sunnah in Nigeria secondary school. Developing good moral and ethical character in learners has become an important matter in this age of globalization. Religious education curricula currently in use in Nigeria completely focused on learner’s academics achievement. The rate of immorality and many other social vices among the youths particularly those who are secondary school leavers is alarming. Against this background, the study focuses on teachers’ reflection on the Qur’an and Prophetic Sunnah to foster students’ intellectual upliftment and cultivate Islamic ethical values in them. The researcher purposively selected six teachers from selected secondary school in Ilorin, Kwara State, Nigeria. The results of semi-structured interviews revealed that the participant teachers believed that reflection on the Qur’an and Prophetic traditions has the potential to instil knowledge, cultivate intellectual skills and inculcate good values and Islamic ethics in the learners. It was also found that insufficient period, negligent attitudes of parents towards their children’s education as well as students’ lack of interest had to some extent influenced teachers’ effort to fully implement the curriculum to inculcate the right type of values in the students.